The human-initiated model of wolf domestication – An expansion based on human-dingo relations in Aboriginal Australia - Brumm, Adam; Germonpré, Mietje; Koungoulos, Loukas (Frontiers in Psychology, 2023)
The historically known relationship of interspecies companionship between Aboriginal foraging communities in Australia and free-ranging dingoes provides a model for understanding the human-canid relations that gave rise to the first domesticated dogs. Here, we propose that a broadly similar relationship might have developed early in time between wild-living wolves and mobile groups of foragers in Late Pleistocene Eurasia, with hunter-gatherers routinely raiding wild wolf dens for pre-weaned pups, which were socialized to humans and kept in camp as tamed companions (“pets”). We outline a model in which captive wolf pups that reverted to the wild to breed when they were sexually mature established their territories in the vicinity of foraging communities — in a “liminal” ecological zone between humans and truly wild-living wolves. Many (or most) of the wolf pups humans took from the wilderness to rear in camp may have derived from these liminal dens where the breeding pairs had been under indirect human selection for tameness over many generations. This highlights the importance of the large seasonal hunting/aggregation camps associated with mammoth kill-sites in Gravettian/Epigravettian central Europe. Large numbers of foragers gathered regularly at these locations during the wild wolf birthing season. We infer that if a pattern of this kind occurred over long periods of time then there might have been a pronounced effect on genetic variation in free-ranging wolves that denned and whelped in the liminal zones in the vicinity of these human seasonal aggregation sites. The argument is not that wolves were domesticated in central Europe. Rather, it is this pattern of hunter-gatherers who caught and reared wild wolf pups gathering seasonally in large numbers that might have been the catalyst for the early changes leading to the first domesticated dogs — whether in western Eurasia or further afield.